Kewenangan Ayah Biologis Menjadi Wali Nikah Bagi Anak Hasil Zina Menurut Pandangan Imam Syafi’i dan Putusan Mahkamah Konstitusi (MK) NO. 16/PUU-VIII/2010 - Agung Sahbana Nasution; Sutrisna Sutrisna; Syarifah Gustiawati (Fakultas Syariah IAIN Laa Roiba Bogor, 2022)
The presentence of marriage guardian is a must which should be considered. This research learn about Imam syafi'i viewpoint and Mahkamah Konstitusi Decision no 16-VIII-PUU/2010 about the authority of bioligical father to be marriage guardian for his out of marriage children.This purpose research is to analyst how Imam Syafii viewpoint and Mahkamah Konstitusi Decision about the authority of bioligical father to be marriage guatdian for his out of marriage children. This research is using yuridis normatif proccess with deskriptip kualitatif method. The result of this research is imam syafii gave 2 viewpoint about bioligical father to be marriage guardian for his out of marriage children. First, its allowed a father to be marriage guardian for his out of marriage children with provision the daughter born at least 6 month after her parents akad. Meanwhile, mahkamah konstitusi decision said